Knowledge about coronavirus disease (COVID-19) in dentists from Lima and Callao - Borja Villanueva, César Andrés (2020)
Aim: Due to its transmission routes and the characteristics of coronavirus disease, odontology is considered a high-risk profession. This study aims to determine the level of knowledge about Coronavirus disease 2019 among dentists in Lima and Callao, Peru. Material and Methods: An observational, descriptive, cross-sectional study was carried out. Licensed dentists from the provinces of Lima and Callao were evaluated using a virtual questionnaire, previously validated by experts, including 15 questions to measure the study variable in addition to 5 additional items to collect general information such as age, sex, region of work, professional experience and the main clinical work. Results: A total of 1047 dentists were included in the study. In the dimensions of knowledge, most dentists were found to have an intermediate level regarding the origin, symptoms, and diagnosis of COVID-19 and in relation to disease risk and transmission; and control measures. Conclusions: Dentists who have a high level of knowledge about COVID-19 are characterized by being male, working in the districts of central Lima, having more than 11 years of professional experience, and performing periodontics / implantology as their main clinical work.